Defining project success - H. Kerzner; V. Ghyoot (South African Journal of Business Management, 1983)
The authors explain why an understanding of the meaning of success is crucial to the achievement of project success; examine the definitions of project success found in the literature and make some suggestions regarding the meaning of project success.
Keywords: 650